Integrasi Text-to-Image dan Generative Pre-Trained Transformer dalam Pengembangan Wisata Edukasi Ramah Anak Usia Dini - Aruna, Alby; Surya, Eka Putri; Prasetyo, Abdul Rahman; Marcelliantika, Adinda; Wijaya, Ginanjar Atma (IAI Nasional Laa Roiba Bogor, 2024)
The integration of Text-to-Image and Generative Pre-Trained Transformer (GPT) technologies in developing child-friendly educational tourism aims to create interactive and engaging learning experiences. This program combines artificial intelligence and digital visualization to produce educational materials tailored to children's developmental needs. The methods used include technical training for tourism managers, development of AI-based interactive content, and evaluation of program effectiveness through observation and user feedback. Results indicate that the use of this technology enhances children's learning interest and makes the educational process more enjoyable. The implementation of AI technology is expected to support innovative educational tourism development and promote cognitive development in early childhood.